MINAT SISWA TERHADAP LAGU DAERAH DI KELAS Xl IPA SMA NEGERI 10 PONTIANAK - Ella, Serafina; Ghozali, Imam; Muniir, Asfar (Universitas Tanjungpura, 2023)
This study was conducted to explore the factors that influence students' interest in folk songs in class XI science of SMA Negeri 10 Pontianak. The research used a qualitative method with a descriptive form and focused on students and teachers of the Cultural Arts subject. Data were collected through observation, interviews, and documentation and analyzed using data reduction, data presentation, and data verification stages. The study found both internal and external factors related to students' interest in folk songs. Internal factors included students' knowledge and enthusiasm for folk songs, but interest was limited to following the rigid curriculum. Students preferred contemporary pop songs for self-development. External factors included a lack of support from the school, as it lacked facilities for exploring music, and parents prioritized academic scores over developing folk song skills. Overall, the study highlights the importance of creating an environment that supports and encourages students' interest in folk songs.